3D Bioprintable Self-Healing Hyaluronic Acid Hydrogel with Cysteamine Grafting for Tissue Engineering - Kasula Nagaraja; Amitava Bhattacharyya; Minsik Jung; Dajeong Kim; Mst Rita Khatun; Insup Noh (Gels)
The abundance of hyaluronic acid (HA) in human tissues attracts its thorough research in tissue regenerating scaffolds and 3D bioprintable hydrogel preparation. Though methacrylation of HA can lead to photo-crosslinkable hydrogels, the catalyst has toxicity concerns, and the hydrogel is not suitable for creating stable complex 3D structures using extrusion 3D bioprinting. In this study, a dual crosslinking on methacrylated HA is introduced, using cysteamine-grafted HA and varying concentrations of 2-hydroxy ethyl acrylate. The resultant hydrogel is suitable for extrusion 3D printing (or bioprinting), mechanically robust, self-standing, stable in phosphate-buffered saline at 37 °C for more than 42 days, has high water absorption capacity with a low swelling ratio (1.5), and exhibits self-healing and adhesive properties. Complex 3D structures like ears and pyramid shapes with more than 2 cm of height are 3D printed using the optimized composition. All the synthesized hydrogels have shown nontoxicity and cell-supportiveness. Loading of cells, tetracycline, and bovine serum albumin into the hydrogel led to better bioink properties such as cell attachment, growth, and proliferation for osteoblast cells. The test results suggest that this hydrogel is biocompatible and has potential for 3D bioprinting of self-standing structures in bioink form in tissue engineering and regenerative medicine.